Anti-CD123 antibody-modified niosomes for targeted delivery of daunorubicin against acute myeloid leukemia - Fu-rong Liu; Hui Jin; Yin Wang; Chen Chen; Ming Li; Sheng-jun Mao; Qiantao Wang; Hui Li (Taylor & Francis Group, 2017)
A novel niosomal delivery system was designed and investigated for the targeted delivery of daunorubicin (DNR) against acute myeloid leukemia (AML). Anti-CD123 antibodies conjugated to Mal-PEG2000-DSPE were incorporated into normal niosomes (NS) via a post insertion method to afford antibody-modified niosomes (CD123-NS). Next, NS was modified with varying densities of antibody (0.5 or 2%, antibody/Span 80, molar ratio), thus providing L-CD123-NS and H-CD123-NS. We studied the effect of antibody density on the uptake efficiency of niosomes in NB4 and THP-1 cells, on which CD123 express differently. Our results demonstrate CD123-NS showed significantly higher uptake efficiency than NS in AML cells, and the uptake efficiency of CD123-NS has been ligand density-dependent. Also, AML cells preincubated with anti-CD123 antibody showed significantly reduced cellular uptake of CD123-NS compared to control. Further study on the uptake mechanism confirmed a receptor-mediated endocytic process. Daunorubicin (DNR)-loaded H-CD123-NS demonstrated a 2.45- and 3.22-fold higher cytotoxicity, compared to DNR-loaded NS in NB4 and THP-1 cells, respectively. Prolonged survival time were observed in leukemic mice treated with DNR-H-CD123-NS. Collectively, these findings support that the CD123-NS represent a promising delivery system for the treatment of AML.